International Multidisciplinary Microscopy Congress Proceedings of InterM, Antalya, Turkey, October 10-13, 2013 - Polychroniadis, Efstathios K.; Oral, Ahmet Yavuz; Ozer, Mehmet (Springer Proceedings in Physics, 2014)
The International Multidisciplinary Microscopy Congress (INTERM2013) was organized on October 10-13, 2013. The aim of the congress was to bring together scientists from various branches to discuss the latest advances in the field of microscopy. The contents of the congress have been broadened to a more "interdisciplinary" scope, so as to allow all scientists working on related subjects to participate and present their work. These proceedings include 39 peer-reviewed technical papers, submitted by leading academic and research institutions from over 12 countries and representing some of the most cutting-edge research available. The 39 papers are grouped into the following sections: - Applications of Microscopy in the Physical Sciences - Applications of Microscopy in the Biological Sciences.